2018
DOI: 10.1002/tox.22537
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidic acid induces apoptosis of human leukemic HL‐60 cells via c‐Jun N‐terminal kinase‐regulated caspase‐8/‐9/‐3 activation pathway

Abstract: Cantharidin, a natural toxin from blister beetles, has shown potent anticancer activities on many solid tumor cells. Recently, cantharidin and its analogue, norcantharidin, were also shown to suppress nonsolid tumors such as chronic myeloid leukemia, acute myeloid leukemia (AML), and leukemic stem cells. However, there is no available information to address the effects of cantharidic acid (CAC), a hydrolysis product of cantharidin, on human AML cells. The present study showed that CAC, at a range of concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Many natural phytochemical products can suppress cell proliferation by arresting cells at vital phases in the cell cycle and triggering apoptosis . Our results indicated that coronarin D inhibits cell growth by inducing cell cycle arrest in the G2/M phase in human Huh7 and Sk‐hep‐1 cells (Figure A).…”
Section: Discussionmentioning
confidence: 73%
“…Many natural phytochemical products can suppress cell proliferation by arresting cells at vital phases in the cell cycle and triggering apoptosis . Our results indicated that coronarin D inhibits cell growth by inducing cell cycle arrest in the G2/M phase in human Huh7 and Sk‐hep‐1 cells (Figure A).…”
Section: Discussionmentioning
confidence: 73%
“…Our results showed that OI treatment time-dependently activated proteolytic cleavage of inactive pro-caspase-9 into its active form, whereas expression level of activated caspase-8 was unaffected (Figure 3b-d). Since the extrinsic apoptotic pathway includes caspase-8 activation, while caspase-9 is involved in the intrinsic mitochondria pathway [30], our findings prompted us to hypothesize that OI compound could activate the mitochondrial caspase-dependent apoptotic pathway, in both MCF-7 and HeLa cells.…”
Section: Oi Triggers Apoptotic Cell Death In Mcf-7 and Hela Cellsmentioning
confidence: 97%
“…HeLa and MCF-7 cells were maintained in DMEM-F12 medium (Sigma-Aldrich, Milan, Italy) containing 10% fetal bovine serum (FBS, Sigma-Aldrich, Milan, Italy), 2 mM L-glutamine (Sigma-Aldrich, Milan, Italy) and 1% penicillin/streptomycin (Sigma-Aldrich, Milan, Italy), as previously reported [29]. MCF-10A cells were cultured in DMEM-F12 supplemented with 10% horse serum (HS, Sigma-Aldrich, Milan, Italy) [30], 2 mM L-glutamine, 1% penicillin/streptomycin, 0.5 mg/mL hydrocortisone (Sigma-Aldrich, Milan, Italy), 20 ng/mL human epidermal growth factor (hEGF, Scheme 1. The in vitro anticancer properties of 5-(carbamoylmethylene)-oxazolidin-2-ones (OA-OI).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Cantharidin (CTD) is found to be the major bioactive component of mylabris. In recent studies, it has been found that CTD and its derivatives, such as Cantharidic acid and norcantharidin, inhibited leukemia cell proliferation, induced apoptosis, caused cell cycle arrest, and potentiated the inhibitory effects of chemotherapy drugs ( , 2001 ; Dorn et al., 2009 ; Liao et al., 2011 ; Sun et al., 2016 ; Wang et al., 2018 ). However, the potential molecular mechanisms are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%